An acceptance, role transition, and couple dynamics-based program for caregivers: A qualitative study of the experience of spouses of persons with young-onset dementia. (November 2020) - Larochette, Clotilde; Wawrziczny, Emilie; Papo, David; Pasquier, Florence; Antoine, Pascal
Objective: In this study, we assessed a support program based on acceptance, role transition, and couple dynamics for spouses of people with young-onset dementia. The qualitative feedback from the caregivers' experience is analyzed. The goal was to explore how this home-based support program is perceived and to appraise the impact of the different approaches that were offered. Design: A thematic analysis was conducted on the answers to the end-of-session questionnaires and the follow-up semistructured interviews. Results: Five themes emerged from the analyses. They highlighted caregivers' ability to overcome their emotional struggle as well as the control of their loved one's behaviors. The results also showed the possibility for caregivers to access new ways to support their loved ones and to maintain the quality of their relationship. Conclusion: These findings represent preliminary evidence of this program's efficacy for caregivers.